Krisis Regenerasi Petani Muda Di Tengah Industialisasi (Studi Fenomenologi Di Desa Blimbing, Kecamatan Gatak, Kabupaten Sukoharjo) - Adilest, Johan; Trinugraha, Yosafat Hermawan; Purwanto, Danang (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
Development in the context of industrialization, land conversion from agricultural land to industrial sector land to be built for factories, development in the context of industrialization has positive and negative impacts. Industrialization is a shift in livelihood from agrarian to industrial. The younger generation with industrialization prefers not to work as farmers anymore, which is a hereditary occupation. The research problem will focus on how the regeneration crisis of young farmers occurs in the midst of industrialization, which is analyzed using James S. Coleman's Rational Choice theory. The method used by researchers is a descriptive qualitative approach, collecting data using a purposive sampling technique, and for data analysis using data triangulation. In James S. Coleman's theory of rational choice there are two important points namely, actors and resources, the actor in question is youth and resources are agricultural land, agricultural science, labor and capital controlled by youth. There are three things that clarify how the action or choice is selected, the first is collective behavior, youth in Blimbing Village raises collective awareness that in determining a career so that they can get and maximize profits when choosing to work non-agricultural both in terms of income, working hours, workload, etc. Two Norms, Granting a factory construction permit, with the emergence of a regional regulation regarding the industrial development plan for the Sukoahrjo district for 2018-2038. Third, corporate actors, government support in transforming paddy fields to become dry land ready to build makes rice field owners prefer to dry rice fields and sell them rather than being used for farming. In the end, by looking at and carefully considering the youth, they prefer not to work as farmers.